Collaboration to Accelerate Proteogenomics Cancer Care: The Department of Veterans Affairs, Department of Defense, and the National Cancer Institute's Applied Proteogenomics OrganizationaL Learning and Outcomes (APOLLO) Network. Issue 5 (May 2017) - Fiore, LD; Rodriguez, H; Shriver, CD
Abstract : A tri‐federal initiative arising out of the Cancer Moonshot has resulted in the formation of a program to utilize advanced genomic and proteomic expression platforms on high‐quality human biospecimens in near‐real‐time in order to identify potentially actionable therapeutic molecular targets, study the relationship of molecular findings to cancer treatment outcomes, and accelerate novel clinical trials with biomarkers of prognostic and predictive value.